A new heterometallic Cu(II)-Cd(II) complex based on 1, 3, 5-benzenetricarboxylic acid. Issue 3 (4th March 2018) - Sun, Qiao-Zhen; Pan, Jun-Qiao; Chai, Li-Yuan; Zhang, Bing-Guang; Liu, Na-Wei; Liu, Hui
Abstract: A novel heterometallic complex [Cu2 Cd2 (OH)(BTC)(TMA)(H2 O)2 ]n (1 ) (H3 BTC = 1, 3, 5-benzenetricarboxylic acid, H4 TMA = 2-hydroxytimesic acid) is synthesized and characterized. The crystal structure analysis reveals that two crystallographically independent Cu(II) ions are both five-coordinate in distorted square pyramidal surroundings. And for two Cd(II) ions, Cd1 is six coordinated, displaying a distorted triangular prism; Cd2 is five-coordinated, fabricating a distorted trigonal bipyramid. In 1, the H3 BTC ligand is partially oxidized into H4 TMA, with bridging mode of μ 8 - and μ 7 - for TMA 4− and BTC 3−, respectively. Thus, 1 presents a 3D structure with (5, 6, 7, 9)-connected net topology.